Leanness score of value stream maps (2007)
A Value Stream Map (VSM) allows lean practitioners to visualize the performance and conditions of manufacturing systems. While creating visibility for improvement plans, a measure of overall leanness level is not inherent in the map. This research proposes a methodology to measure the overall leanness of a VSM considering Cost, Time and output Value. Value-added and non-value-added investments are identified to quantify the level of leanness. Using the Data Envelopment Analysis technique, the leanness measure delivers a self-contained, unit-invariant score of the mapped system to support decision making on continuous improvement.